Factors affecting management earnings forecast in corporate governance structure: Evidence in China - LI, XUEJIN (2019)
This paper selects the seven factors from the perspective of corporate governance to research how these factors affect the management earnings forecast accuracy for voluntary disclosures. These factors include the size of the board of directors, the proportion of independent directors, the size of the board of supervisors, the CEO duality, management compensation, management shareholding ratio and equity concentration. The results of empirical study demonstrate that there is no significant relationship between the size of the board of directors, the size of the board of supervisors, management compensation and the veracity of management profits forecast. In addition, the CEO duality, the high management shareholding ratio, the high concentration of equity could increase the management profits forecast accuracy. Conversely, the higher the proportion of independent directors can lower the accuracy of management earnings forecast. When robust error test and robustness test are performed, the significant results and correlation coefficients do not change significantly, therefore the empirical results have a certain degree of persuasiveness.